2015
DOI: 10.1002/etc.3151
|View full text |Cite
|
Sign up to set email alerts
|

Mercury concentrations in different tissues of turtle and caiman species from the Rio Purus, Amazonas, Brazil

Abstract: Total mercury (Hg) concentrations of muscle, liver, blood, and epidermal keratin were measured in typically consumed, economically and culturally important species of turtle (Podocnemis unifilis and Podocnemis expansa) and caiman (Melanosuchus niger and Caiman crocodilus) from the Rio Purus in the Amazon basin, Brazil. Methylmercury (MeHg) concentrations were also measured in muscle tissue, representing the first analysis of MeHg concentrations in Amazonian reptile species. In muscle tissues Hg was mostly MeHg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 49 publications
3
17
1
Order By: Relevance
“…Few ecotoxicological studies focused on freshwater turtles exist [(Thompson et al, 2018) but see (Lu et al, 2019; Tada et al, 2007)], with most focusing on fish due to their economic importance and use as a food resource (Duponchelle et al, 2021; Moran et al, 2018). Despite this, the presence of mercury has been documented in turtles from temperate (Burger and Gibbons, 1998; Meyer et al, 2014; Slimani et al, 2018) and tropical regions (Eggins et al, 2015; Schneider et al, 2009; Schneider et al, 2010). As freshwater turtles are often consumed by riverside populations there is a strong potential for freshwater turtles to represent a source of dietary methylmercury (Green et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Few ecotoxicological studies focused on freshwater turtles exist [(Thompson et al, 2018) but see (Lu et al, 2019; Tada et al, 2007)], with most focusing on fish due to their economic importance and use as a food resource (Duponchelle et al, 2021; Moran et al, 2018). Despite this, the presence of mercury has been documented in turtles from temperate (Burger and Gibbons, 1998; Meyer et al, 2014; Slimani et al, 2018) and tropical regions (Eggins et al, 2015; Schneider et al, 2009; Schneider et al, 2010). As freshwater turtles are often consumed by riverside populations there is a strong potential for freshwater turtles to represent a source of dietary methylmercury (Green et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported positive correlations between body size and Hg concentration in aquatic turtles, including Chelydra serpentina [ 24 ], Chelodina parkeri , Heosemys spinosa , Leucocephalon yuwonoi , Malaclemys terrapin [ 41 ], Podocnemis erythrocephala [ 20 ], and Podocnemis unifilis [ 43 ]. Among Chelydra serpentina , Sternotherus odoratus , Chrysemys picta , and Pseudemys rubriventris , the older and larger individuals tend to have proportionally higher Hg concentrations than the younger and smaller individuals [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study, with the turtle species Podocnemis unifilis, Podocnemis expansa, Podocnemis erythrocephala, Podocnemis sextuberculata, Peltocephalus dumerilianus and Chelus fimbriatus, the same authors observed that muscle was considered to be a good predictor of Hg (Schneider et al, 2010), demonstrating interspecific differences in mercury concentrations likely due to different feeding habits and foraging behaviour. In the same year, Eggins et al (2015) demonstrated that blood was a better predictor of Hg compared to scales for M. niger and was able to predict 72% of variation in muscle tissues and 61% of variation in liver tissues. Keratin, in contrast, showed low predictability (47% of variation in muscle tissues and 32% of variation in liver tissues) and was unreliable.…”
Section: Biological Dimensionmentioning
confidence: 98%